Implications of Teacher Interpersonal Communication Ability on Student Learning Motivation in Islamic Religious Education Lessons During Pandemi - Amin, Alfauzan; Alimni, Alimni; Kurniawan, Dwi Agus; Triani, Elza; Pratama, Wahyu Adi (Journal of Education Reseach and Evaluation, 2022)
During the pandemic, teachers' interpersonal communication skills are needed to create student learning motivation. So this research needs to be done with the aim of this research is to determine the effect of interpersonal communication skills of teachers on students' motivation in learning Islam Religious Education during the pandemic at SMPN 20 Jambi City and SMPN 20 Bengkulu. This type of research is Mix method research. The number of sample respondents is 72 students. Data collection techniques using Random Sampling. In the hypothesis test, it was found that in the T test, it was found that there was a significant difference in the teacher’s Interpersonal Communication ability and students’ learning motivation in Islamic religious education subjects in each school and the results of the regression test showed that there was an influence between Teacher Interpersonal Communication on students’ learning motivation in the subjects. Islamic religious education lessons during the pandemic.